2018
DOI: 10.3389/fimmu.2018.00104
|View full text |Cite
|
Sign up to set email alerts
|

A20/Tumor Necrosis Factor α-Induced Protein 3 in Immune Cells Controls Development of Autoinflammation and Autoimmunity: Lessons from Mouse Models

Abstract: Immune cell activation is a stringently regulated process, as exaggerated innate and adaptive immune responses can lead to autoinflammatory and autoimmune diseases. Perhaps the best-characterized molecular pathway promoting cell activation is the nuclear factor-κB (NF-κB) signaling pathway. Stimulation of this pathway leads to transcription of numerous pro-inflammatory and cell-survival genes. Several mechanisms tightly control NF-κB activity, including the key regulatory zinc finger (de)ubiquitinating enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 142 publications
(228 reference statements)
5
112
0
Order By: Relevance
“…It has also been shown that A20 expression is reduced in the lungs of subjects with asthma compared with healthy controls . In the present study, we have confirmed this observation demonstrating that A20 expression is significantly reduced in lung tissue biopsies, as well as in circulating leucocytes collected from patients with asthma in comparison with healthy subjects, supporting the concept that A20 is an important endogenous modulator of inflammatory responses …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has also been shown that A20 expression is reduced in the lungs of subjects with asthma compared with healthy controls . In the present study, we have confirmed this observation demonstrating that A20 expression is significantly reduced in lung tissue biopsies, as well as in circulating leucocytes collected from patients with asthma in comparison with healthy subjects, supporting the concept that A20 is an important endogenous modulator of inflammatory responses …”
Section: Discussionsupporting
confidence: 90%
“…20 In the present study, we have confirmed this observation demonstrating that A20 expression is significantly reduced in lung tissue biopsies, as well as in circulating leucocytes collected from patients with asthma in comparison with healthy subjects, supporting the concept that A20 is an important endogenous modulator of inflammatory responses. 25,26 The role of A20 in inflammatory conditions has been well doc-…”
Section: This Disparity Between the Pharmacokinetic And Pharmacodynamicmentioning
confidence: 99%
“…IL‐1α is released after tissue damage or death and participates in the inflammatory response (Afonina et al, 2011). TNFAIP3 plays important roles in innate and adaptive immune cells, including the control of necroptosis and inflammasome activity (Das, Chen, Hendriks, & Kool, 2018; Vande et al, 2014). In addition, BNIP3 is involved in various cellular processes and is considered a key regulator of apoptosis (Vasagiri & Kutala, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The requirement of A20 for tissue homeostasis is highlighted by the 234 fact that the A20 locus has been associated with many autoimmune and inflammatory 235 disorders by GWAS (53). Further to this, A20 haploinsufficient human subjects present with 236 increased TH17 cells and inflammatory disease (21,22), whereas mice with A20 germline 237 deficiency succumb to uncontrolled inflammation (54). 238…”
Section: Discussion 208mentioning
confidence: 99%